2020
DOI: 10.1007/s10802-020-00705-9
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Family’s Emotional Climate in the Links between Parent-Adolescent Communication and Adolescent Psychosocial Functioning

Abstract: The current study was designed to extend the parenting literature by testing the moderating role of the family’s emotional climate, operationalized with parent-adolescent emotional closeness and adolescent feelings of being overly controlled by parents on the longitudinal associations between parent-driven communication efforts (i.e. parental behavioral control and solicitation of information from their adolescent), adolescent-driven communication efforts (i.e. adolescent disclosure and secrecy) and adolescent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
35
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 57 publications
5
35
1
2
Order By: Relevance
“…Fourth, other possible moderators that might influence the association, e.g., parental stress, sensitivity, or mentalizing ability, were not controlled for. Finally, this study only investigated the effects of parent-driven communication, not child-driven communication, which might have different effects on adolescent depressive symptoms ( Kapetanovic et al, 2020 ; Kapetanovic and Skoog, 2021 ). Further studies should examine the different roles of parent-driven and child-driven communication.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, other possible moderators that might influence the association, e.g., parental stress, sensitivity, or mentalizing ability, were not controlled for. Finally, this study only investigated the effects of parent-driven communication, not child-driven communication, which might have different effects on adolescent depressive symptoms ( Kapetanovic et al, 2020 ; Kapetanovic and Skoog, 2021 ). Further studies should examine the different roles of parent-driven and child-driven communication.…”
Section: Discussionmentioning
confidence: 99%
“…What characterizes adolescents with exacerbated use of alcohol, as well as other substances, such as tobacco and narcotics during the pandemic is yet to be understood. Developmental theories [ 12 ] suggest that parent–child relationships [ 13 ], including close bonds between parents and children [ 14 ] and parental knowledge of adolescents’ whereabouts [ 15 ], as well as adolescent involvement with peers [ 16 ] are critical social factors that have an impact on adolescent behavior and adjustment, including substance use. Indeed, one Swedish study of 755 adolescents and the trajectories of their alcohol and drug use, as well as criminality, suggested that poor family cohesion and engagement with deviant peers, are important explanatory factors for problematic behavioral development, including substance use issues [ 17 ].…”
mentioning
confidence: 99%
“…Throughout the life course, family communication is crucial for a balanced family system and involves the exchange and sharing of information, knowledge, values, and beliefs ( 6 , 19 ). The content of family communication and type of information being shared can shape behaviors, emotions, and sense of self ( 20 , 21 ), and may thus influence family and individual wellbeing. In addition to providing support against social isolation and loneliness during the pandemic, family communication can also be an important source of health information ( 22 , 23 ).…”
Section: Introductionmentioning
confidence: 99%